FACTORS INFLUENCING STUDENTS' DECISION IN CHOOSING UNIVERSITIES: BUILD BRIGHT UNIVERSITY STUDENTS - Por, Narith; Say, Chanminea; Mov, Socheat (Jurnal As-Salam, 2024)
This research assesses the factors influencing students' decision-making when choosing a university. The study proposes eight factors, such as parental or guardian influence, high school teacher recommendations, graduate quality, colleague recommendations, location, school fees, learning environment, and university reputation, on students' university choices. A quantitative approach was employed, utilizing both secondary and primary data. A total of 330 students were sampled for this study. The data were analyzed using SPSS, employing descriptive statistics for data summarization and inferential statistics for analysis. Descriptive tools such as frequency analysis were used to examine the distribution of responses, while regression analysis was conducted to test the predictive power of the factors. The findings of this study indicate that factors such as parental or guardian influence, high school teacher recommendations, graduate quality, colleague recommendations, location, school fees, learning environment, and university reputation are all significant considerations in students' decision-making process when choosing a university. These factors play an influential role in shaping students' preferences and choices. The results show that these factors significantly impact students' university choices. The study contributes to the existing literature by providing empirical evidence on the importance of these factors in the decision-making process. Understanding the influence of these factors can assist universities in developing targeted strategies to attract and meet the needs of prospective students. By recognizing the significance of parental involvement, fostering positive relationships with high school teachers, showcasing successful graduates, promoting positive word-of-mouth recommendations, providing a conducive learning environment, and building a solid reputation, universities can enhance their appeal and effectively compete in the higher education market. Further research in this area can explore additional factors and delve deeper into the mechanisms influencing students' decision-making when choosing a university.